Conjunctions in Polish sign language dictionaries and signed texts translated from Polish - Kozub, Monika (Taikomoji kalbotyra, 2024)
This study conducts a comparative analysis of conjunctions catalogued in Polish Sign Language (PJM) dictionaries, from historical to contemporary editions, and those used in actual PJM texts translated from Polish. The analysis includes dictionaries from the earliest known Słownik mimiczny dla głuchoniemych i osób z nimi styczność mających (1879) to the contemporary online Korpusowy słownik polskiego języka migowego UW (2016). The main focus of this article is to examine the frequency of certain PJM conjunctions in texts translated by an all-Deaf team. This is exemplified by the multimedia adaptation of the fifth-grade primary school textbook Jutro pójdę w świat 5 (2016), in which all texts are translated into PJM. The results aim to bridge the gap between lexicographical records and actual language use in the deaf community, and to highlight the dynamics of PJM development.